Programmes of Industrial Development 1956-61 (D. Chemical and Allied Industries) - Planning Commission (Planning Commission, 1959)
When the First Five Year Plan was published towards the end of 1952, there was brought out at the same time a volume entitled “Programmes of Industrial Development, 1951-56” containing studies of 42 organised industries. In the present volume, there are gathered together statistical data relating to 51 organised industries together with programmes for their expansion during the period of the Second Five Year Plan. All the industries covered by the previous volume have again been included and the following have been added : (1) Structural fabrication (2) Industrial machinery (3) Ferro-manganese (4) Coal carbonisation (5) Dyestuffs and intermediates (6) Refractories (7) Rubber manufactures (8) Coated abrasives (9) Plastics (10) Starch and glucose (11) Biscuits and confectionery and (12) Fruit and vegetable preservation. Textile machinery and machine tools treated separately in the earlier volume are dealt with under Industrial machinery, and Grinding wheels and Coated abrasives are treated together so that the number of organised industries in this volume comes to 51. These 51 industries account for about 90 per cent of the fixed investment in organised manufacturing industries at the present time. 2. The material relating to the various individual industries have been presented, so far as possible, in a uniform manner. Facts and figures are first given regarding the progress made in the past five years, with special reference to the targets proposed in the First Plan, and thereafter the expansions or developments envisaged during the next five years are set forth. In the case of industries not included in the previous volume, a brief history of the development up to the beginning of 1956 has been supplied.
Government of India Planning Commission